A proposed in-service education program in health education based on the competency needs of the Olongapo Elementary School teachers - Manlutac, Lucila M. 1934- (s.n.], 1969)
The aim of the study is to find out the comptency needs of the Olongapo Elementary School teachers in Health Education and with the knowledge of the needs as basis, to propose an in-service education program in Health Education.